ARTIFICIAL INTELLIGENCE (AI) IN EDUCATION: STRENGTHS AND DRAWBACKS - Anarbekova Gulzodabegim Nazirjon qizi; Namozova Dilobar; Sharipova Muxlisa (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Artificial intelligence (AI) technologies are advancing rapidly,significantly impacting all aspects of life. This transformation is increasingly evident,particularly with the increased adoption of generative AI tools such as ChatGPT. Educational systems are experiencing the most substantial effects in this area. On the one hand, the growth of such systems in the labor market has created an urgent need for educational institutions to quickly reorganize schooling in response to skill changes in professions. However, difficult considerations arise regarding whether and how these systems should be incorporated into education, if at all, as well as how to handle ethical concerns brought on by AI systems. From the viewpoints of students, instructors, and administrators, this study assesses the probable advantages and hazards of implementing AI systems in educational systems. The pertinent research on the possible advantages and disadvantages of AI from various scholarly databases was taken into account in the systematic review. As a result, the study addresses the possible applications of AI systems in education as well as any potential hazards.